Dimensi Autentik Multimodalitas Konteks Kultural dalam Pragmatik Edukasional - Permatasari, Agmi Sinta Nanda (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examined the authentic dimensions of multimodality of cultural context in educational pragmatics and its significance in understanding culture. The aim is to describe the cultural context using multimodality elements with data sources in the form of TikTok content containing cultural aspects. This research used descriptive qualitative methods with reading and note-taking techniques. The theories were related to authentic dimensions, multimodality, and cultural context. The results showed that culture's values, rules, and social systems can be explained effectively through a multimodality approach that includes visual, gestural, aural, and linguistic aspects. The cultural value system in the tradition of the Suling Dewa dance in Bayang Village shows belief values conveyed through various modalities. The rules and social systems in the tradition of Kerik Gigi of the Mentawai tribe and the use of silk sarong in the Bugis community show that cultural rules and social status are explained and understood through multimodality, helping to transmit cultural knowledge effectively from generation to generation. In conclusion, understanding culture through multimodality is essential in this era of globalization to remain relevant and effective in learning. It can enhance mutual respect for cultural differences and intercultural communication in educational and social environments.